EVALUASI PROSES PERIZINAN PELAYANAN TERPADU SATU PINTU (PTSP) DALAM RANGKA PERWUJUDAN GOOD GOVERNANCE (Studi penelitian : UPT PTSP Provinsi Jawa Tengah) - agnes anindita krisilvana; Teguh yuwono .; Nunik Retno herawati (Journal of Politic and Government Studies, 2017)
ABSTRACTIn the current era of reform the system of government based on absolute good governance to be applied, especially in the implementation of public services. The implementation of public services no longer aims only to meet statutory or considers administrative matters alone, but about government accountability and promote community. Implementation of good governance should be applied at the One Stop Services (OSS) which is where the licensing services ranging from application stage to the stage of issuance of documents in one place. The purpose of this study is to see how far the application of the principles of good governance in the One Stop Central Java Province. In addition, to determine the factors of success and constraints faced in the implementation of the licensing service towards good governance. This research uses descriptive quantitative and qualitative approaches. The data were obtained from questionnaires, interviews with informants, observation, and documentation. This study uses a case study approach.The conclusion of this study indicate that the quality of the services contained in UPT PTSP Central Java province has been referring to the principles of good governance. There are success factors of the background for good governance are among others the implementation of information technology-based services, the absence of charge, PTSP staff who dared to act decisively reject the fraud, and procurement licensing outlets outside the area of the city of Semarang. In addition there are also constraints encountered include the completion of licensing is not timely, the lack of availability of employees, complexity of licensing online filing, and a lack of security or back up to the front office employee. Advice can be given that is more clarified the timing of licenses, in increased numbers of employees in UPT PTSP, online licensing restyled with in facilitates and shorten, and in perkuatnya security or backing up.Keyword : Evaluation, Public Service, One Stop Services